2017
DOI: 10.15171/jlms.2017.s11
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Plasma Treatment of Cercon® Zirconia Ceramics on Adhesion to Resin Composite Cements and Surface Properties

Abstract: Introduction:In recent years, the use of ceramic base zirconia is considered in dentistry for all ceramic restorations because of its chemical stability, biocompatibility, and good compressive as well as flexural strength. However, due to its chemical stability, there is a challenge with dental bonding. Several studies have been done to improve zirconia bonding but they are not reliable. The purpose of this research is to study the effect of plasma treatment on bonding strength of zirconia. Methods: In this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 40 publications
4
35
1
5
Order By: Relevance
“…These were in accordance with many researches (5,27,28) . Valverde et al (29) found a significant increase in the bond strength to zirconia surfaces when cold plasma was applied alone or in combination with alumina sandblasting.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These were in accordance with many researches (5,27,28) . Valverde et al (29) found a significant increase in the bond strength to zirconia surfaces when cold plasma was applied alone or in combination with alumina sandblasting.…”
Section: Discussionsupporting
confidence: 92%
“…Surface energy (SE) is a term describing the intermolecular forces of the material surface, depending on polar and disperse constituents of the surface (30) . There is an opposite correlation between the SE of a surface and contact angle measurements of liquids (5) .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, aimed at achieving better adhesion between Y‐TZP and resin cement, we chose to perform tests using Cercon Zirconia, which has previously been used to test strategies in the improvement of bond strength . According to our results, the PECVD technique and the Si‐based film deposited on the specimens promoted higher roughness on the surfaces tested compared with the polished group.…”
Section: Discussionmentioning
confidence: 99%